Understanding the Safety Profile of Imatinib in Asian Chronic Myeloid Leukemia Patients: A Systematic Review - Budiarti, Niky; Ikawati, Zullies; Nurrochmad, Arief; Arief, Thendi Abdul (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Background: The treatment of chronic myeloid leukemia has advanced substantially since the introduction of tyrosine kinase inhibitors, particularly imatinib. However, adverse events associated with imatinib may affect adherence and quality of life, highlighting the importance of understanding safety outcomes across populations.Objective: This systematic review aimed to synthesize evidence on hematologic and non-hematologic adverse events associated with imatinib use among chronic myeloid leukemia patients in Asia.Methods: A systematic literature search was conducted in PubMed, Scopus, and ScienceDirect for studies published between January 2020 and July 2025. Eligible studies were synthesized narratively due to methodological heterogeneity. Adverse events were extracted as reported and graded using standardized toxicity criteria, and causality assessment was applied when available. Study quality was evaluated using established critical appraisal tools. Five studies from India, China, and Taiwan met the inclusion criteria.Results: The most frequent hematologic adverse event was anemia, followed by neutropenia and thrombocytopenia. Common non-hematologic adverse events included gastrointestinal symptoms, peripheral or periorbital edema, muscle cramps, and hyperpigmentation, with regional variations. Most events were mild to moderate (grades 1–2), while severe fluid retention, including pleural and pericardial effusions, was reported in isolated cases. No studies reported permanent discontinuation of imatinib due to adverse events.Conclusion: This review summarizes imatinib-related adverse events among chronic myeloid leukemia patients from selected Asian regions—East and South Asia, specifically India, China, and Taiwan—showing predominantly mild to moderate toxicities and providing practice-informed insights for clinical monitoring. However, the absence of data from other Asian regions precludes generalization to the entire Asian continent.